Impact of COVID-19 pandemic on the oral health condition of diabetic patients in Al-Qassim, Saudi Arabia - Majed M. Aljarallah; Khaled A. Alturaifi; Saad M. AlHarbi; Fahad O. Alanazi; Faris A. Alghidani; Abdurahman S. Alotaiq; Daij al Daiji; Jihad Alokaily; Hussain A. AlQahtani; Ibtisam A. Alburikan; Abdurahman M. Aljarallah (Genius Journals, 2022)
The present study aimed to assess the awareness of diabetic patients in Al-Qassim, Saudi Arabia, about the relationship between diabetes, oral health, and the COVID-19 pandemic. Materials and Methods: A cross-sectional questionnaire-based survey was conducted following systematic random sampling in four medical centers in Al-Qassim. Survey responses to 19 multiple choice questions were collected from 120 participants and subsequently analyzed
Keywords: Al-Qassim; Saudi Arabia; diabetes; dentist